1978
DOI: 10.1073/pnas.75.12.6069
|View full text |Cite
|
Sign up to set email alerts
|

Loss of proliferative calcium dependence: simple in vitro indicator of tumorigenicity.

Abstract: The proliferative activities of three lines of "normal" epithelioid rat liver cells and six tumorigenic liver cell lines in the presence of a wide range of calcium concentrations were measured by a simple colony forming assay. The proliferative activities of the normal clis and, to a lesser extent, of the cells of a marginally tumorigenic line were directly proportional to the extracellular calcium concentration. The proliferative activities of the cells of the strongly tumorigenic lines, on the other hand, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Similar ion lowering has been shown to arrest the proliferation of normal, but not of neoplastic, cells in studies by other investigators (14,15). By use of this chicken heart mesenchymal cell system, I have now attained an almost qualitative separation in the proliferative behavior of normal and RSV-infected cells-i.e., an in vitro autonomy effect under physiological conditions.…”
mentioning
confidence: 76%
“…Similar ion lowering has been shown to arrest the proliferation of normal, but not of neoplastic, cells in studies by other investigators (14,15). By use of this chicken heart mesenchymal cell system, I have now attained an almost qualitative separation in the proliferative behavior of normal and RSV-infected cells-i.e., an in vitro autonomy effect under physiological conditions.…”
mentioning
confidence: 76%
“…Perhaps, a similar mechanism is in force in transformed fibroblasts. In addition, it has also been shown that transformed cells require a lower calcium concentration than normal cells in order to survive (Swierenga et al 1978;Borek 1980). This change in the necessary calcium concentration may also be related to changes in the Na+/K + equilibrium since a number of calcium-activated potassium channels which respond to the calcium ion concentration are present in cells (Hille 1984).…”
Section: Discussionmentioning
confidence: 97%
“…It can be concluded, that the most active was combination of RJ-F(M) and HuIFN-αN3 2:1, where the level of the GSH was 24.9±2. 4 Future experiments will show whether these GSH-and MDA-related activities of RJ-F (M), HuIFN-αN3, 10-HDA and their combinations may cause the decrease of the tumorigenicity index of different tumour cells in vitro, as previously reported in the literature (27,28), also through their tumorigenic potential. This is important for the practical use of royal jelly (10-HDA) and HuIFN-αN3 in a combination that could be of value for future development of tumour therapy based on the use of bioactive compounds.…”
Section: Gsh Determination and Measurement Of Lipid Peroxidationmentioning
confidence: 93%